Desempenho de láparos em ninhos com bagana de carnaúba como substrato alternativo de nidificação - Nogueira, Fatima Alice Machado (2024)
The aim was to evaluate the use of carnauba leaf mulch as an alternative nesting substrate for rabbits, compared to wood shavings, assessing the thermoregulatory and physiological responses of the rabbits and lizards. Thirteen New Zealand White rabbits were used, divided into two treatments: the control considering the use of wood shavings as a nesting substrate (T1) and carnauba leaf mulch as a nesting substrate (T2), with seven rabbits in the wood shavings treatment and six rabbits in the mulch treatment, the rabbit with the litter being considered the experimental unit. Reproductive management was carried out through natural mating and three days before the expected delivery date, a wooden nest was placed with a 5 cm high layer of substrate, according to each treatment. The evaluation parameters were climatic variables, in which the temperature and relative humidity of the air were recorded. The surface temperature of the nests (TSN), the surface temperature of the larvae's skin (TSP) and the internal temperature of the nest (TIN) were evaluated. A significant difference was identified between the TIN of the two treatments, where T1 showed that the wood shavings reached a higher internal temperature than the carnauba leaf mulch, but neither treatment reached the right temperature for the larvae. Concerning TSN, and TSP, there was no significant difference (P<0.05) between the treatments. The greatest differences were seen in the performance parameters of the larvae up to 42 days old, in which carnauba leaf mulch promoted a higher average weight gain per larvae, but when the number of animals per treatment and the maternal effect between them were evaluated, the difference between treatments was minimal, thus proving the possibility of replacing wood shavings with carnauba leaf mulch as a nesting substrate.